Pelaksanaan Program Peningkatan Literasi Politik Mahasiswa pada Unit Kegiatan-Wadah Pengkajian dan Pengembangan Sosial Politik Universitas Negeri Padang - Nurwahyuni, Nurwahyuni; Rafni, Al; Suryanef, Suryanef; S, Nurman (Journal of Civic Education, 2024)
This study examines the implementation of political literacy improvement programs by UK-WP2SOSPOL to enhance students' political knowledge. A qualitative descriptive method was used, with data collected through interviews and secondary sources such as websites, journals, and supporting documents. Informants included Student Affairs Expert Staff, Advisors, the Executive Board and UK-WP2SOSPOL members. The findings reveal two key stages in program implementation: planning and execution. Activities include social-political classes, public discussions, and bulletin publications. Supporting factors include organizational capabilities and the commitment of program implementers. However, challenges include weak organizational management, causing delays in execution, and limited dissemination of information beyond UK-WP2SOSPOL members, restricting broader student participation. This study highlights the need for improved organizational strategies and wider outreach efforts to ensure the program’s success. Strengthening management capabilities and expanding communication channels to engage a broader audience are recommended to maximize the impact of political literacy initiatives.